Maximum Individual Wave Height Prediction Using Different Machine Learning Techniques with Data Collected from a Buoy Located in Bilbao (Bay of Biscay) - Lucia Porlan-Ferrando; J. David Nuñez-Gonzalez; Alain Ulazia Manterola; Nahia Martinez-Iturricastillo; John V. Ringwood (Journal of Marine Science and Engineering, 2025)
Accurate prediction of extreme waves, particularly the maximum wave height and the ratio between the maximum and significant wave heights of individual waves, is crucial for maritime safety and the resilience of offshore infrastructure. This study employs machine learning (ML) techniques such as linear regression modeling (LM), support vector regression (SVR), long short-term memory (LSTM), and gated recurrent units (GRU) to develop predictive models based on historical data (1990–2024) obtained from a buoy at a specific oceanic location. The results show that the SVR model provides the highest accuracy in predicting the maximum wave height (Hmax), achieving a coefficient of determination (R2) of 0.9006 and mean squared error (MSE) of 0.0185. For estimation of the ratio between maximum and significant wave heights (Hmax/Hs), the SVR and LM models exhibit comparable performance, with MSE values of 0.0229. These findings have significant implications for improving early warning systems, optimizing the structural design of offshore infrastructure, and enhancing the efficiency of energy extraction under changing climate conditions.

Endophytic and rhizospheric microbial communities associated with native and introduced cultivated plant species in Uruguay as sources for plant growth promotion bioinoculant development - Federico Battistoni; Ana Fernández Scavino; Lucia Ferrando; Adriana Montañez; Fabiana Pezanni; Cecilia Taulé; Patricia Vaz-Jauri (Environmental Sustainability, 2023)

Abundance and diversity of endophytic and rhizospheric diazotrophs associated with rice roots from different rice rotation systems under field conditions - Cecilia Ghiazza; José A. Terra; Lucia Ferrando (Environmental Sustainability, 2023)